Üriner inkontinans hasta eğitiminde solunum ve pelvik taban egzersiz içeriğinin delphi yöntemi ile belirlenmesi - Atalay, Tuğçe (My University, 2023)
Amaç: Pelvik Taban Eğitim programlarının kullanıldığı araştırmalarda pelvik taban kasları (PTK) ve bu kaslar ile sinerjistik çalışan diyaframın etkinliğinin geliştirilmesine yönelik farklı protokoller bulunmaktadır. En etkili tedavi protokolüne ilişkin bir görüş birliği bulunamamıştır. Bu araştırma, kadın sağlığı alanında çalışan fizyoterapist ve hekimlerin, Üriner İnkontinans (Üİ) hasta eğitiminde kullandığı solunum ve pelvik taban egzersiz içeriğinin uzlaşı yöntemi ile oluşturulmasını amaçlamaktadır. Gereç ve Yöntem: Çalışmada Delphi tekniği kullanıldı. Delphi süreci 3 tur planlandı. Birinci tur, Üİ hasta eğitimi içeriği ve egzersiz yöntemlerini içeren 5 açık uçlu sorudan oluştu. İkinci turda, ilk turdaki cevapların içerik analizi yapıldıktan sonra 5’li likert ölçeğinden oluşan maddeler oluşturuldu. Üçüncü turda, ikinci turda uzlaşı sağlanamayan maddeler katılımcılara tekrar gönderildi. Uzlaşı oranı %70 olarak kabul edildi. Çalışma sonunda yapılan panelle uzlaşılan maddeler oluşturuldu. Bulgular: Araştırmaya 30 katılımcı dahil edildi. Birinci turun analizine göre düzenlenen 97 maddelik ikinci tur anketine 30 katılımcı cevap verdi. İkinci tur sonunda 26 maddede uzlaşı sağlandı. Üçüncü turda katılımcılardan uzlaşılmayan maddelere tekrar cevap vermesi istendi. Üçüncü turun sonunda 8 maddede uzlaşıldı. Çalışmacılar tarafından yapılan panel sonucu 34 maddede uzlaşıldı. Sonuç: Üİ alanında uzmanlaşmış ve bu alanda çalışan fizyoterapist ve hekimler hasta eğitiminde PTK ve solunum egzersizlerine yer verilmesi gerektiğini düşünmektedir. Egzersiz bu eğitimin en önemli parçası olmuştur. Egzersiz süresi, sayısı ve sıklığı ile ilgili standardizasyonlara ihtiyaç vardır.

Aim: Different protocols for improving the effectiveness of the pelvic floor (PF) muscles and the diaphragm working synergistically with these muscles were used in studies using Pelvic Floor Training Programs. There was no consensus on the most effective treatment protocol. This research aims to create the content of respiratory and PF exercises used in urinary incontinence (UI) patient education by physiotherapists and doctors working in the field of women's health, by consensus method. Materials and Methods: Delphi technique was used in the study. The Delphi process planned in 3 rounds. The first round consisted of 5 open-ended questions including the content of UI patient education and exercise methods. In the second round, after the content analysis of the answers in the first round, items consisting of a 5-point Likert scale were created. In the third round, the items that could not be agreed in the second round were sent back to the participants. The consensus rate was accepted as 70%. At the end of the study, the agreed items were formed with the panel. Results: 30 participants were included in the study. 30 participants responded to the second round questionnaire consisting of 97 items, which was prepared according to the analysis of the first round. At the end of the second round, consensus was reached on 26 items. In the third round, the participants were asked to respond again to the items that were not agreed upon. At the end of the third round, 8 items were agreed. As a result of the panel made by the researchers, consensus was accepted on 34 items. Conclusion: Physiotherapist and doctors who specialize in and work in the field of UI think that PF muscles and breathing exercises should be included in patient education. Exercise has been the most important part of this training. There is a need for standardizations regarding the duration, number and frequency of exercise.
Determination of breathing and pelvic floor exercise content via delphi method in urinary incontinence patient education
Keywords: Fizik tedavi; Fizik tedavi modaliteleri; hasta eğitimi urinary incontinence; patient education; pelvic floor; pelvik taban; Physical therapy; Physical Therapy Modalities; respiratory training; solunum eğitimi; üriner inkontinans